Energy balance in JET. (August 2017) - Matthews, G.F.; Bunting, P.; Devaux, S.; Drewelow, P.; Guillemaut, C.; King, D.B.; Lerche, E.; Silburn, S.; Szepesi, G.; Riccardo, V.; Thompson, V.; ,
Highlights: A full analysis of the energy balance in JET is presented. Typically, 25% of the energy input is missing with low scatter. Energy densities on the main wall appear consistent with bolometer reconstruction. It remains unclear whether the missing energy is due to errors in inputs or losses. Radiation limits are meaningless without proper error analysis. Abstract: In this paper we discuss results from the study of the energy balance in JET based on calculated heating energies, radiated energy from bolometry and tile calorimetry. Recent data enables us to be more confident in the numbers used and to exclude certain possibilities but the overall energy imbalance which typically amounts to 25% of total input remains unexplained. This shows that caution is required in interpreting fractional radiated powers which are commonly used to measure the effectiveness of impurity seeded scenarios at reducing divertor heat load.